QOL-45. PROFILES OF EXECUTIVE FUNCTIONS IN SURVIVORS OF PEDIATRIC BRAIN TUMOR. A COMPREHENSIVE APPROACH. Issue 2 (22nd June 2018) - Roche, Jeanne; Chevignard, Mathilde; Gall, Didier Le; Frappaz, Didier; Roulin, Jean-Luc; Roy, Arnaud
Abstract: Executive functions (EF) are a collection of distinct but related high-level processes, of major importance during development. They are frequently impaired following childhood brain tumors, with negative consequences on academic achievement and overall independence. This study aimed at performing a comprehensive assessment of EF domains, using a combination of performance-based tasks and a daily life questionnaire. We developed a novel test battery (FEE), based on Diamonds' developmental framework of EF (2013), comprised of 10 subtests assessing flexibility, inhibition, working memory, and planning, controlling for lower level processes (i.e. language, visual-spatial skills). Outcome measures include different performance indicators (e.g. number of errors, time...). Twenty-seven children treated for various brain tumors and 27 matched healthy controls, performed the FEE battery, as well as the parent- and teacher-ratings of the Behavior Rating Inventory of Executive Functions (BRIEF) questionnaire. The association between performance-based and rating measures of EF was also examined. Patients performed significantly worse than controls on some, but not all subtests. The main finding was that overall, patients performed tasks slower than controls, without significantly more errors. Correlations between performance-based tasks and the BRIEF questionnaire were weak and not significant, as most often reported in the literature. This study allowed identification of a specific dysexecutive profile that should be confirmed in a larger sample of pediatric brain tumor survivors. These findings could lead to improvements in EF assessment, to better understanding of EF deficits basis (i.e. the cognitive cost of slow information processing) and their consequences, and development of targeted interventions.